Child sexual abuse and subsequent offending and victimisation: A 45 year follow-up study - Emily Mann
This study investigates whether a disproportionate number of CSA victims subsequently perpetrate offences and experience future victimisation compared with people who have not been sexually abused. In a sample of 2,759 CSA victims who were abused between 1964 and 1995, it was found CSA victims were almost five times more likely than the general population to be charged with any offence than their non-abused counterparts, with strongest associations found for sexual and violent offences. CSA victims were also more likely to have been victims of crime, particularly crimes of a sexual or violent nature. This research highlights the need for therapeutic interventions targeted at adolescent male CSA victims, particularly with regard to offender treatment programs, where many programs currently do not allow for exploration of offenders’ own sexual victimisation